High-protein diets reduce plasma pro-inflammatory cytokines following lipopolysaccharide challenge in Swiss Albino mice - Hellen W. Kinyi; Charles Kato Drago; Lucy Ochola; Gertrude N. Kiwanuka (PLoS ONE, 2025)
Macronutrients serve as principal sources of energy, structural components, and regulators of physiological processes. However, the optimal macronutrient combination for health remains unclear. While previous studies indicate that dietary macronutrient composition influences immune function, many have examined individual nutrients in isolation, failing to reflect the interactive effects of macronutrients. This study addresses this gap by examining how varying ratios of dietary carbohydrates, proteins, and lipids modulate serum cytokine responses to lipopolysaccharide challenge in Swiss albino mice. Male and female Swiss albino mice (n = 6 per group), aged 6–8 weeks, were randomly assigned to six purified isocaloric diets with differing macronutrient ratios for 15 weeks. Body weights were monitored to assess nutritional status. Serum levels of TNF-α, IL-6, IL-1β, and IL-10 were measured in unchallenged mice and after three hours of intraperitoneal LPS administration. Mice fed high-carbohydrate, low-protein diets had the highest weight (33.1 g ± 1.1), while those on high-lipid, low-protein diets had the lowest (28.3 g ± 0.6). Plasma levels of TNF-α and IL-10 varied significantly (p < 0.05) by diet in the unchallenged mice. IL-1β did not differ markedly (p = 0.085) across the dietary groups, and IL-6 levels were below the assay’s detection limit (<230.312 pg/mL). Following the lipopolysaccharide challenge, all cytokines increased, with significant differences among diets. Mice on high-protein diets exhibited notably lower TNF-α, IL-6, and IL-1β levels compared to those on high-carbohydrate or high-lipid diets. In contrast, IL-10 levels were higher in mice fed low-protein, high-carbohydrate, or high-lipid diets. In conclusion, high-protein diets appeared to dampen the responsiveness to lipopolysaccharide challenge, as indicated by smaller increases in pro-inflammatory cytokine levels, whereas high-carbohydrate and high-lipid diets elicited greater cytokine responses. We recommend that nutritional strategies aimed at modulating inflammation should ensure adequate dietary protein to help protect against both acute and chronic inflammation.